Missing the Beat: Adult Learning Through Religious Music in an African American Church - Michael L. Rowland (Adult Education Research Conference, 1999)
The purpose of this study was to understand the ways religious music contributes to learning and meaning making for African American adults within American society. Retrospective biographies were used to understand how the religious musical experiences of African American adults affect learning. The findings of the study are discussed.